2016
DOI: 10.1007/s40889-016-0017-8
|View full text |Cite
|
Sign up to set email alerts
|

Moral perception, educational environment, and development of medical professionalism in medical students during the clinical rotations in Peru

Abstract: The aim of this study was to determine the relationship between a clinical environment and the development of empathy, teamwork, and lifelong learning in medical students who are doing their first clinical rotation. The Jefferson Scales of Empathy (JSE), Jefferson Scale of Attitudes toward Physician-Nurse Collaboration (JSAPNC), and Jefferson Scale of Physician Lifelong Learning (JeffSPLLL) were administered to 60 sixth-year medical students, before and after their first clinical rotation in five health care i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
3
12
0
1
Order By: Relevance
“…Similarly to the two versions of the empathy scale, the differences between the two versions of the JeffSPLL are in the rewording of those items where the term "medicine" is used, in order to make it more applicable to students from other healthcare areas. The JeffSPLL tool has demonstrated a high reliability and validity in both student groups in different cultural contexts (Muliira et al, 2012;San-Martín et al, 2016;Tuirán-Gutiérrez et al, 2019).…”
Section: Main Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to the two versions of the empathy scale, the differences between the two versions of the JeffSPLL are in the rewording of those items where the term "medicine" is used, in order to make it more applicable to students from other healthcare areas. The JeffSPLL tool has demonstrated a high reliability and validity in both student groups in different cultural contexts (Muliira et al, 2012;San-Martín et al, 2016;Tuirán-Gutiérrez et al, 2019).…”
Section: Main Measuresmentioning
confidence: 99%
“…Finding out whether a long exposition to a hierarchical environment influences how medicine students develop their attitudes toward inter-professional collaboration with nurses is an important educational concern (Fox et al, 2018). Regarding this issue, a recent study performed in five Peruvian public hospitals showed that abilities toward interprofessional collaborative work did not improve in medicine students after 3 months of clinical training in those hospitals, as could be initially expected (San-Martín et al, 2016). These preliminary findings suggest that, in the absence of targeted interdisciplinary educational programs, the social environment acquires an important role of influence in the development of inter-professional collaborative work abilities.…”
Section: Introductionmentioning
confidence: 96%
“…A good learning environment will spur student learning reasons, also what and how students will learn, so students will have high independence in learning [8]. In clinical clerkship stage (the stage of the medical profession), a good learning environment will trigger the development of lifelong learning abilities, and the development of attitude [9]. Medical students' perceptions of the learning environment can influence academic behavior and development.…”
Section: Discussionmentioning
confidence: 99%
“…At the clinical clerkship stage, the learning environment has an influence on the development of professionalism and lifelong learning. Some factors that influence this include age and gender [9]. Stress that comes from the learning environment can trigger the weakness of the memory of medical students [4].…”
Section: Discussionmentioning
confidence: 99%
“…Una fortaleza de este estudio es que ha explorado la percepción del ambiente educativo de 6 años académicos. Además, aunque un estudio peruano utilizó el DREEM para evaluar una rotación hospitalaria 30 , este es el primer estudio que lo utiliza para evaluar globalmente la totalidad de las etapas preclínica y clínica. Sin embargo, este estudio también presenta algunas limitaciones.…”
Section: Fortalezas Y Limitacionesunclassified